Fundamental Solutions in the Generalized Theory of Thermoelastic Diffusion with Triple Porosity - KANSAL, Tarun (Engineering Transactions, 2023)
The main aim of this paper is to derive the basic governing equations for an anisotropic thermoelastic medium with mass diffusion and triple porosity. Additionally, the fundamental solutions of a system of equations for steady, pseudo-, quasi-static oscillations and equilibrium are also constructed.